Integration processes in the global economy: current state and prospects:the cases of the European Union, ASEAN Economic Community, and NAFTA - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2016)
The aim of the paper is to determine the current state of the integration processes in the global economy and prognosticate on the foreseeable changes in this phenomenon in the upcoming. Will they be divergence from or continuity with the past trends in the global economy in this field? The article examines three regional integration groupings, i.e. the European Union, ASEAN Economic Community, and NAFTA. The analysis makes it possible to conclude that all of these groupings/organizations are encountering some problems. In the case of the EU, these are mainly: the two - speed integration process as far as a monetary union is concerned; serious negative consequences of the global financial crisis for the socio-economic cohesion of the EU-28; as well as a worsening position in the world trade in goods and services and in the total global gross capital inflows. The problems of the ASEAN Economic Community seem to be connected with some discrepancies between the political will in favour of deepening integration among member states and the real economic difficulties involved in attaining higher stages of integration among a group of countries extremely differentiated in their economic development. NAFTA's problems also lie in the asymmetrical development between member states, as well as in the lessening importance of the integration within the organization for the member states, which results from the putting into effect numerous other FTAs. The growing openness of all the analyzed integration groupings, being in line with the globalization process, seems to be a future characteristic of integration processes in the global economy.
Keywords: 330; Global economy; integration; European Union; ASEAN Economic Community; NATFA